MENGATASI MASALAH BELAJAR DENGAN STRATEGI PEMBELAJARAN BERBASIS MULTIPLE INTELEGENSI - Asna Mardin; Azrul Azrul (Universitas Negeri Padang, 2023)
The instructional process must be appropriate with the talents, interests and physical and psychology developments of student (The Government Regulation, number 32 point 19 year 2013). When there is an incompatibility, so it would be trouble learning, such as: students are difficult to take a change of their behavior permanently and trouble to develop their potential itself. The instructional problems may come from student itself, such as: the diversity of learning styles, and physical and psychology development. But it can be occurred because of external factor. One way to overcome these problems is using a multiple intelligence-based instructional strategy, so that the learning is suitable with the talent, interest and physical and psychology development of student. Because of the diversity of individual differences in a class, it may be difficult to give special services to each student. Implication of this diversity, the teacher needs to pay attention to multiple intelligences resonance in the process of instructional.